A lithium iron manganese phosphate material and its preparation process

Through the combination of co-precipitation method and titanium/silica aerogel, the conductivity of lithium manganese iron phosphate material and the diffusion rate of lithium ions are improved, and the problems of poor conductivity and slow diffusion rate of the material are solved, which significantly improves its electrochemical performance.

CN119218965BActive Publication Date: 2025-03-18HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718584.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-18
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Lithium manganese ferrophosphate material has poor electrical conductivity and slow diffusion rate of lithium ions, which affect its electrochemical performance.

Method used

Lithium manganese iron phosphate material was prepared by co-precipitation method, and titanium/silica aerogel was added to the process to improve the electronic structure of the material and the diffusion path of lithium ions through the titanium atoms and silicon atom frame in the titanium/silica aerogel.

Benefits of technology

The conductivity of lithium manganese iron phosphate material and the conduction efficiency of lithium ions are significantly improved, the electron transmission path is optimized, and the overall electrochemical performance of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a lithium iron manganese phosphate material and a preparation process thereof. Titanium / silicon dioxide aerogel is added to the lithium iron manganese phosphate material during the preparation process, and an iron source, a manganese source and a phosphorus source are co-precipitated on the titanium / silicon dioxide aerogel, so that iron ions and manganese ions can be kept in a stable and uniform valence state, and the dissolution of manganese can be reduced; and the material with a three-dimensional configuration can be constructed, and the silicon atom framework can also improve the stability of the material, and provide a highly conductive network for the transmission of lithium ions and the transfer of electrons. The doping of titanium atoms can change the electronic structure of the material, increase the conductivity of the material, further accelerate the conduction efficiency of lithium ions, optimize the transmission path of electrons, and solve the problems of poor conductivity of the lithium iron manganese phosphate material and slow lithium ion diffusion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium manganese iron phosphate material and a preparation process thereof. Background Art

[0002] Among the positive electrode materials for lithium-ion batteries, phosphate positive electrode materials are the most representative. Lithium iron phosphate and lithium manganese phosphate in phosphate positive electrode materials are both commonly used lithium-ion positive electrode materials. Both have stable olivine structure and theoretical specific capacity. Compared with lithium iron phosphate, lithium manganese phosphate has a higher redox potential, which can provide higher energy density. Despite this, the ion conductivity and ion kinetics of both materials are low, especially under high rate conditions, lithium manganese phosphate is more difficult to obtain high capacity than lithium iron phosphate. In order to overcome these problems, combining the advantages of the two, iron and manganese are co-doped in phosphate positive electrode materials to obtain the maximum energy density and rate performance.

[0003] However, this lithium manganese iron phosphate material also has two inherent defects. One is that the strong PO bonds in the material structure restrict the free movement of electrons, resulting in low electronic conductivity and poor electrical conductivity; the other is that the one-dimensional lithium ion diffusion path of the material leads to slow transmission rate, limited energy storage capacity, and affects its electrochemical properties. Summary of the invention

[0004] The object of the present invention is to provide a lithium iron manganese phosphate material and a preparation process thereof, so as to solve the problems of poor conductivity and slow lithium ion diffusion rate of the lithium iron manganese phosphate material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a process for preparing a lithium iron manganese phosphate material, comprising the following process steps:

[0007] S1. Adding a manganese source, an iron source and a phosphorus source to deionized water and stirring to mix to prepare a premix;

[0008] S2. Add titanium / silicon dioxide aerogel to the premixed liquid, disperse for 15 to 30 minutes to form a suspension, raise the temperature to 80 to 90° C. under a nitrogen atmosphere, stir and react for 2 to 3 hours to form a precipitate, and then filter, wash and dry to obtain a pre-reactant;

[0009] S3. The pre-reactant was mixed with a lithium source and ball-milled for 2 to 3 hours, calcined at high temperature for 8 to 9 hours under an inert gas atmosphere, and cooled to obtain lithium iron manganese phosphate powder;

[0010] S4. Add lithium manganese iron phosphate powder and carbon source into deionized water and mix well, filter and heat treat for 2 to 3 hours to obtain lithium manganese iron phosphate material.

[0011] Preferably, the mass ratio of titanium / silicon dioxide aerogel to phosphorus source is (1.1-1.4):1.

[0012] Preferably, the molar ratio of the phosphorus source, the manganese source, the iron source and the lithium source is 1: (0.3-0.6): (0.4-0.7): (0.95-1.1).

[0013] Preferably, the phosphorus source includes one or more combinations of phosphoric acid, lithium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate, iron phosphate, manganese phosphate, sodium phosphate, lithium phosphate, pyrophosphoric acid and sodium pyrophosphate.

[0014] Preferably, the iron source includes a combination of one or more of iron powder, iron oxide, iron nitrate, iron carbonate, iron phosphate, ferrous oxalate dihydrate and ferrosoferric oxide.

[0015] Preferably, the manganese source includes a combination of one or more of manganese dioxide, manganese dichloride, manganese tetraoxide, manganese sulfate, manganese carbonate, manganese oxalate and manganese phosphate.

[0016] Preferably, the lithium source includes one or more combinations of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium hydroxide, lithium carbonate, lithium oxalate, lithium chloride, lithium acetate and lithium phosphate.

[0017] Preferably, the carbon source comprises a combination of one or more of sucrose, starch, glucose, organic acid, carbonate, citric acid, sodium acetate, polyethylene glycol, polyethylene diene and polyvinyl alcohol.

[0018] Preferably, the mass ratio of the carbon source to the lithium iron manganese phosphate powder is (0.1-0.2):1.

[0019] Preferably, the high temperature calcination temperature is 600-800°C; the heat treatment temperature is 300-400°C.

[0020] By adopting the above technical scheme, the co-precipitation method is adopted in the preparation of lithium manganese iron phosphate material in the present invention. The lithium manganese iron phosphate material prepared by this method has a small and evenly distributed particle size. Such particle characteristics are conducive to improving the charge and discharge performance of lithium-ion batteries and enhancing the overall electrochemical properties of the material.

[0021] In addition, the present invention adds titanium / silicon dioxide aerogel during the preparation process. Iron source, manganese source and phosphorus source are deposited on the aerogel by coprecipitation. On the one hand, titanium / silicon dioxide aerogel can act as a reducing agent, which can stably reduce iron ions and manganese ions to a divalent state, promote them to be closely combined together, and effectively avoid the phenomenon of manganese dissolution caused by the small particle size of the material; on the other hand, titanium / silicon dioxide aerogel provides a framework structure for lithium iron manganese phosphate material, and constructs a material with a three-dimensional configuration, which changes the original one-dimensional diffusion path of lithium ions and transforms it into a three-dimensional network structure. The highly crystalline structure of the three-dimensional network and the close interface bonding between the network structures provide more active centers for the subsequent adsorption and intercalation of lithium ions, and also enhance the conductivity of the electron transmission path; finally, the aerogel provides a highly conductive network for the transmission of lithium ions and the transfer of electrons, significantly improves the conduction efficiency of lithium ions, and optimizes the electron transmission path, thereby effectively solving the problems of poor conductivity of lithium iron manganese phosphate material and slow diffusion rate of lithium ions.

[0022] At the same time, the titanium / silicon dioxide aerogel used in the present invention also introduces a silicon atom framework and titanium atoms into the lithium iron manganese phosphate material. On the one hand, the silicon atom framework can improve the structural stability of the material and reduce the shedding of active substances. On the other hand, it can provide a more orderly diffusion channel for lithium ions, reduce the diffusion resistance of lithium ions, and thus improve the transmission efficiency of lithium ions. At the same time, silicon, as a high-capacity material, can significantly improve the energy density of the lithium iron manganese phosphate material, making its specific capacity closer to the theoretical value, thereby improving the rate performance of the material.

[0023] The doping of titanium atoms can change the electronic structure of lithium manganese iron phosphate materials. Since titanium has a smaller ionic radius, it can significantly speed up the electron transfer efficiency of the material. After carbon coating, the titanium atoms and carbon atoms work together to further improve the conductivity of the material, thereby improving the charge and discharge efficiency of the battery. The introduction of titanium atoms not only optimizes the electronic structure of the material, but also improves the diffusion path of lithium ions, making their migration channel smoother. This improvement helps to improve the rate performance of the material and ensure that good electrochemical performance is maintained at high current density.

[0024] Preferably, the raw materials of titanium / silicon dioxide aerogel include titanium precursor and tetraethyl orthosilicate in a molar ratio of (0.2-0.4):1.

[0025] Preferably, the titanium precursor includes a combination of one or more of tetrabutyl titanate, ethyl titanate and tetraisopropyl titanate.

[0026] Preferably, the titanium / silicon dioxide aerogel is prepared according to the following method: adding a titanium precursor and an acid catalyst to a solvent, adding tetraethyl orthosilicate and water after stirring to dissolve, carrying out a sol-gel reaction in a water bath at 60 to 65° C., and aging in a water bath at 50 to 60° C. for 5 to 7 days to obtain the titanium / silicon dioxide aerogel after the gel is formed.

[0027] Preferably, the molar ratio of water to tetraethyl orthosilicate is (0.8-1):1.

[0028] Preferably, the solvent includes a combination of one or more of ethanol, methanol, isopropanol, ethylene glycol and n-butanol.

[0029] Preferably, the acid catalyst comprises a combination of one or more of hydrochloric acid, nitric acid, sulfuric acid and acetic acid; and the added amount of the acid catalyst is 0.02 to 0.05 mol / L.

[0030] By adopting the above technical solution, the present invention adds a titanium precursor during the preparation of the silica aerogel, and the titanium precursor and tetraethyl orthosilicate participate in the sol-gel reaction together, thereby introducing titanium atoms into the aerogel. After aging treatment, the titanium / silicon dioxide aerogel structure formed is more stable, and can provide a stable three-dimensional framework for the lithium iron manganese phosphate material. This three-dimensional framework helps to form a lithium iron manganese phosphate material with a three-dimensional configuration, provides a highly conductive network, accelerates the conduction efficiency of lithium ions, and optimizes the transmission path of free electrons.

[0031] And by doping titanium atoms, the electronic structure of the formed lithium manganese iron phosphate material can be changed, thereby improving the overall electronic conductivity. It not only helps to speed up the transmission rate of free electrons and reduce the restriction of PO bonds on free electrons, but also can optimize the migration channel of lithium ions and further improve the defects of the lithium manganese iron phosphate material itself.

[0032] Preferably, the titanium / silicon dioxide aerogel is modified by carboxymethyl cellulose; the mass ratio of the carboxymethyl cellulose to the titanium / silicon dioxide aerogel is (0.25-0.5):1.

[0033] Preferably, the titanium / silica aerogel is modified according to the following method: carboxymethyl cellulose is added to a solvent, and after dissolution, the titanium / silica aerogel is added, and refluxed at 80-90° C. for 6-8 hours, and finally washed and dried to obtain the titanium / silica aerogel modified with carboxymethyl cellulose.

[0034] Preferably, the solvent comprises a combination of one or more of water, sodium hydroxide aqueous solution and ethanol aqueous solution.

[0035] The titanium / silica aerogel has a high content of silanol on its surface and tends to aggregate when added to the premix, which affects the morphology control, particle size and distribution uniformity of the lithium manganese iron phosphate material, thereby affecting the rate performance and electrochemical properties of the lithium manganese iron phosphate material.

[0036] By adopting the above technical solution, the titanium / silica aerogel is modified. The dispersibility of the titanium / silica aerogel after carboxymethyl cellulose modification is significantly improved, which helps to better control the size and distribution uniformity of the particles and inhibit the agglomeration of the aerogel. In addition, carboxymethyl cellulose, as a derivative of natural polysaccharides, can provide more active centers for lithium ions and optimize the diffusion path of lithium ions after carboxymethyl cellulose modification. At the same time, it can also enhance the binding force between the iron source, manganese source and titanium / silica aerogel in the preparation process of lithium iron manganese phosphate material, and improve the overall structural stability of the material.

[0037] In addition, the titanium / silica aerogel modified with carboxymethyl cellulose can be used as an in-situ carbon source during high-temperature calcination to form a good conductor inside the lithium manganese iron phosphate material, increase the transmission path of free electrons, and help build a three-dimensional electron conduction network. The secondary carbon source coating technology can significantly improve the electronic conductivity of the material, and enhance the material's rate performance and specific capacity.

[0038] In a second aspect, the present invention provides a lithium iron manganese phosphate material prepared by the above-mentioned preparation process of the lithium iron manganese phosphate material.

[0039] Beneficial effects of the present invention:

[0040] 1. The present invention adopts a co-precipitation method to prepare lithium iron manganese phosphate material, wherein titanium / silicon dioxide aerogel is added, which can keep iron ions and manganese ions in a stable and uniform valence state and reduce the dissolution of manganese; and can help construct a material with a three-dimensional configuration, providing a highly conductive network for the transmission of lithium ions and the transfer of electrons. At the same time, the silicon atom framework can improve the stability of the material, and the doping of titanium atoms can change the electronic structure of the material, increase the conductivity, further accelerate the conduction efficiency of lithium ions, optimize the transmission path of electrons, and enhance the conductivity of the material.

[0041] 2. The titanium / silicon dioxide aerogel of the present invention is also modified by carboxymethyl cellulose, which can improve the dispersibility of the titanium / silicon dioxide aerogel, is beneficial to the morphology control of the lithium iron manganese phosphate material, improves the stability and density of the three-dimensional network, and can also serve as an in-situ carbon source to increase the transmission path of free electrons and improve the electronic conductivity of the material. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Preparation Example

[0044] Preparation Example 1: A titanium / silicon dioxide aerogel is prepared according to the following method:

[0045] 0.03 mol of tetrabutyl titanate and hydrochloric acid were added to 250 mL of ethylene glycol, wherein the concentration of the hydrochloric acid was 0.03 mol / L. After stirring and dissolving, 0.1 mol of ethyl orthosilicate and 0.1 mol of water were added. The sol-gel reaction was carried out in a water bath at 60°C. After the gel was formed, it was aged in a water bath at 55°C for 7 days to obtain titanium / silicon dioxide aerogel.

[0046] Preparation Example 2, a titanium / silicon dioxide aerogel, is different from Preparation Example 1 only in that the amount of tetrabutyl titanate added is 0.02 mol.

[0047] Preparation Example 3, a titanium / silicon dioxide aerogel, is different from Preparation Example 1 only in that the amount of tetrabutyl titanate added is 0.04 mol.

[0048] Preparation Example 4, a titanium / silicon dioxide aerogel, is different from Preparation Example 1 only in that the amount of water added is 0.08 mol.

[0049] Preparation Example 5, a titanium / silicon dioxide aerogel, is different from Preparation Example 1 only in that the amount of tetrabutyl titanate added is 0.01 mol.

[0050] Preparation Example 6, a titanium / silicon dioxide aerogel, is different from Preparation Example 1 only in that the amount of tetrabutyl titanate added is 0.05 mol.

[0051] Preparation Example 7, a silica aerogel, is different from Preparation Example 1 only in that tetrabutyl titanate is not added.

[0052] Preparation Example 8, a titanium / silicon dioxide aerogel, is different from Preparation Example 1 only in that the obtained titanium / silicon dioxide aerogel is further subjected to carboxymethyl fiber modification treatment, and the modification is performed according to the following method:

[0053] 3.5 g of carboxymethyl cellulose was added to 250 mL of 20% ethanol aqueous solution, and after dissolution, 10 g of the obtained titanium / silica aerogel was added, and the reaction was refluxed at 85° C. for 8 h. Finally, the titanium / silica aerogel modified with carboxymethyl cellulose was obtained after washing and drying.

[0054] Preparation Example 9, a titanium / silicon dioxide aerogel, is different from Preparation Example 8 only in that the amount of carboxymethyl cellulose added is 2.5 g.

[0055] Preparation Example 10, a titanium / silicon dioxide aerogel, is different from Preparation Example 8 only in that the added amount of carboxymethyl cellulose is 5 g.

[0056] Preparation Example 11, a titanium / silicon dioxide aerogel, is different from Preparation Example 8 only in that the added amount of carboxymethyl cellulose is 1.5 g.

[0057] Preparation Example 12, a titanium / silicon dioxide aerogel, is different from Preparation Example 8 only in that the amount of carboxymethyl cellulose added is 6 g.

[0058] Preparation Example 13, a silica aerogel, is different from Preparation Example 8 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of silica aerogel prepared in Preparation Example 7.

[0059] Example

[0060] Example 1: A lithium manganese iron phosphate material is prepared according to the following process steps:

[0061] S1. Add 0.4 mol manganese carbonate, 0.6 mol ferric nitrate and 1 mol ammonium dihydrogen phosphate into deionized water and stir to mix to prepare a premixed solution, wherein the solid content of the premixed solution is 50%;

[0062] S2. 138 g of the titanium / silicon dioxide aerogel prepared in Preparation Example 1 was added to the premixed liquid and dispersed for 20 min to form a suspension. The temperature was raised to 90 ° C. under a nitrogen atmosphere, and the reaction was stirred for 2 h to form a precipitate, which was then filtered, washed and dried to obtain a pre-reacted product;

[0063] S3. The pre-reactant was mixed with 1 mol of lithium hydroxide and ball-milled for 2 h, and calcined at high temperature for 8 h under a nitrogen atmosphere, wherein the high temperature calcination temperature was 700 ° C, and the lithium iron manganese phosphate powder was obtained after cooling;

[0064] S4. Take 100g of lithium iron manganese phosphate powder and 15g of sucrose and add them to deionized water and mix them evenly. Control the solid content to 40%. After filtering, heat treat for 2h at a heat treatment temperature of 300°C to obtain lithium iron manganese phosphate material with a molecular formula of LiMn 0.4 Fe 0.6 PO4.

[0065] Embodiments 2 to 7 are lithium iron manganese phosphate materials, which differ from Embodiment 1 only in that the raw material ratio of lithium iron manganese phosphate is adjusted, as shown in Table 1:

[0066]

[0067] Among them, Example 2 uses the titanium / silicon dioxide aerogel prepared in Preparation Example 2; Example 3 uses the titanium / silicon dioxide aerogel prepared in Preparation Example 3; Examples 4 and 5 use the titanium / silicon dioxide aerogel prepared in Preparation Example 1; Examples 6 and 7 use the titanium / silicon dioxide aerogel prepared in Preparation Example 4.

[0068] Example 8, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of the titanium / silicon dioxide aerogel prepared in Preparation Example 5.

[0069] Example 9, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of titanium / silicon dioxide aerogel prepared in Preparation Example 6.

[0070] Example 10, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of titanium / silicon dioxide aerogel prepared in Preparation Example 8.

[0071] Example 11, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of titanium / silicon dioxide aerogel prepared in Preparation Example 9.

[0072] Example 12, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of the titanium / silicon dioxide aerogel prepared in Preparation Example 10.

[0073] Example 13, a lithium manganese iron phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of titanium / silicon dioxide aerogel prepared in Preparation Example 11.

[0074] Example 14, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of titanium / silicon dioxide aerogel prepared in Preparation Example 12.

[0075] Example 15, a lithium manganese iron phosphate material, is different from Example 1 only in that the added amount of the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is 115 g.

[0076] Example 16, a lithium iron manganese phosphate material, is different from Example 1 only in that the added amount of the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is 172.5 g.

[0077] Comparative Example

[0078] Comparative Example 1 is a lithium iron manganese phosphate material, which is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of silicon dioxide aerogel prepared in Preparation Example 7.

[0079] Comparative Example 2, a lithium iron manganese phosphate material, is different from Example 1 only in that the titanium / silicon dioxide aerogel prepared in Preparation Example 1 is replaced by an equal amount of silicon dioxide aerogel prepared in Preparation Example 13.

[0080] Comparative Example 3, a lithium manganese iron phosphate material is prepared according to the following process steps:

[0081] S1: dissolving ferric nitrate and manganese carbonate in a molar ratio of 0.4:0.6 in deionized water, adding ascorbic acid, controlling the concentration of ascorbic acid to be 0.005 mol / L, and mixing to prepare a mixed salt solution;

[0082] S2: Under an inert atmosphere, a mixed salt solution is added to a 2.5 mol / L ammonium bicarbonate solution to perform a precipitation reaction, and the molar ratio of total iron and manganese metal ions to bicarbonate ions is controlled to be 1:2.2. After the reaction is completed, aging is performed, and solid-liquid separation is performed to obtain ferrous manganese carbonate;

[0083] S3: mixing the obtained ferrous manganese carbonate and phosphorus pentoxide, wherein the element molar ratio (Fe+Mn):P=1:1, grinding under a nitrogen atmosphere, and heat treating at 550° C. after grinding to obtain ferrous manganese pyrophosphate;

[0084] S4: Mix the obtained manganese ferrous pyrophosphate with lithium chloride and sucrose, wherein the molar ratio of (Fe+Mn):Li:carbon source=1:1:0.3, add to deionized water and mix evenly, control the solid content to 50%, and adjust the pH to 2.5, and carry out hydrothermal reaction in a closed environment for 2 hours. The obtained hydrothermal product is calcined in an inert atmosphere for 8 hours at a calcination temperature of 650°C to obtain lithium iron manganese phosphate material.

[0085] Performance testing

[0086] 1. Sample preparation:

[0087] The lithium iron manganese phosphate material obtained in the embodiment and the comparative example is used as the positive electrode material, the conductive agent is Super P, the binder is polyvinylidene fluoride, the solvent is a dimethyl carbonate (DMC) and ethylene carbonate (EC) solution with a volume ratio of 1:1, the mass ratio of the positive electrode material, the conductive agent and the binder is 8:1:1, the negative electrode is a lithium sheet, the separator is a Celgard 2500 composite membrane, and the electrolyte is a 1 mol / L lithium hexafluorophosphate aqueous solution; the button battery is assembled in a glove box with an argon protective atmosphere.

[0088] 2. Electrochemical performance test:

[0089] The electrochemical performance test of button batteries was carried out using a blue electric test cabinet, the test temperature was 25°C, and the test voltage range was set to 2.2V to 4.3V. The battery was tested for charge and discharge cycle performance, and the discharge specific capacity at 0.1C and 1C was tested.

[0090] The above test results are shown in Table 2:

[0091]

[0092] According to Table 1, in combination with Example 1 and Example 2 to Example 7, it can be seen that there is no significant difference in the discharge specific capacity and cycle capacity retention rate of Example 2 to Example 7 compared with Example 1, indicating that there is no significant difference in the electrochemical performance of Example 2 to Example 7 compared with Example 1. The reason is that compared with Example 1, Example 2 to Example 7 only changes the ratio of raw materials within the required range, which has little effect on the performance of the final lithium manganese iron phosphate material.

[0093] Combining Example 1, Example 8, Example 9 and Comparative Example 1, it can be seen that the discharge specific capacity and cycle capacity retention rate of Example 8 and Comparative Example 1 are both reduced compared with Example 1, and the reduction in Comparative Example 1 is more obvious. The reason is that the content of titanium atoms in the titanium / silicon dioxide aerogel is changed in Example 8, Example 9 and Comparative Example 1, wherein the content of titanium atoms is reduced in Example 8, thereby reducing the improvement of the surface electronic structure of the lithium manganese iron phosphate material by titanium atoms, and the electron transmission efficiency is reduced, resulting in a decrease in electrochemical performance. Comparative Example 1 is not doped with titanium atoms, and the performance degradation is more obvious. In Example 9, the amount of titanium atoms added is increased, and the titanium atoms in the silica aerogel have reached saturation, and the performance of the material will no longer be significantly improved.

[0094] Combining Example 1, Example 10, Examples 11 to 14 and Comparative Example 2, it can be seen that the discharge specific capacity and cycle capacity retention rate of Example 10 are improved compared with Example 1, and the various performances of Examples 11 to 14 and Comparative Example 2 are reduced compared with Example 10. The reason is that the titanium / silicon dioxide aerogel used in Example 10 is modified with carboxymethyl cellulose, which can not only improve the dispersibility of the titanium / silicon dioxide aerogel and help adjust the morphology of the lithium iron manganese phosphate material, but also serve as an in-situ carbon source to improve the overall conductivity of the material, increase the diffusion channel of lithium ions, and improve the electrochemical performance of the material. Compared with Example 10, Example 11 and Example 12 changed the amount of carboxymethyl cellulose added within the required range, so the performance was not significantly affected. However, Example 13 and Example 14 changed the amount of carboxymethyl cellulose added outside the required range. Reducing the amount of carboxymethyl cellulose added did not significantly improve the dispersibility of the titanium / silica aerogel, and had little effect on improving the conductivity. Increasing the amount of carboxymethyl cellulose added would result in an excessive carbon content in the obtained lithium manganese iron phosphate material, inhibiting excessive growth of crystal particles, and further affecting the electrochemical properties of the material.

[0095] Combining Example 1, Example 15, Example 16 and Comparative Example 3, it can be seen that the discharge specific capacity and cycle capacity retention rate of Example 15, Example 16 and Comparative Example 3 are all reduced compared with Example 1, and the reduction in Comparative Example 3 is more obvious. The reason is that Example 15 and Example 16 change the amount of titanium / silicon dioxide aerogel added. When the amount of addition is reduced, the ability to construct a three-dimensional network framework will decrease, and the number of three-dimensional lithium ion diffusion channels will decrease, which is not conducive to the improvement of the electrochemical performance of the material; the increase in the amount of addition will increase the probability of agglomeration of titanium / silicon dioxide aerogel, thereby affecting the morphology control of lithium iron manganese phosphate material and the uniformity of particle distribution, thereby resulting in a decrease in electrochemical performance. In Comparative Example 3, a conventional coprecipitation method is used to prepare lithium iron manganese phosphate material. Although the particle size distribution of the material is improved to a certain extent, compared with Example 1, a material with a three-dimensional configuration is not constructed, and a network structure with high conductivity is not provided for electron transfer, so the performance is significantly reduced.

[0096] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0097] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A preparation process of lithium manganese iron phosphate material, characterized in that: The process steps include: S1. Adding a manganese source, an iron source and a phosphorus source to deionized water and stirring to mix to prepare a premix; S2. Add titanium / silicon dioxide aerogel to the premixed liquid, disperse for 15 to 30 minutes to form a suspension, raise the temperature to 80 to 90° C. under a nitrogen atmosphere, stir and react for 2 to 3 hours to form a precipitate, and then filter, wash and dry to obtain a pre-reactant; S3. The pre-reactant was mixed with a lithium source and ball-milled for 2 to 3 hours, calcined at high temperature for 8 to 9 hours under an inert gas atmosphere, and cooled to obtain lithium iron manganese phosphate powder; S4. Add lithium iron manganese phosphate powder and carbon source to deionized water and mix well, filter and heat treat for 2 to 3 hours to obtain lithium iron manganese phosphate material; The raw materials of the titanium / silicon dioxide aerogel include a titanium precursor and tetraethyl orthosilicate in a molar ratio of (0.2-0.4):1; The titanium / silicon dioxide aerogel is modified by carboxymethyl cellulose; the mass ratio of the carboxymethyl cellulose to the titanium / silicon dioxide aerogel is (0.25-0.5):1; The mass ratio of the titanium / silicon dioxide aerogel to the phosphorus source is (1.1-1.4):

1.

2. The preparation process of lithium iron manganese phosphate material according to claim 1, characterized in that: The titanium precursor includes a combination of one or more of tetrabutyl titanate, ethyl titanate and tetraisopropyl titanate.

3. The preparation process of lithium iron manganese phosphate material according to claim 1, characterized in that: The titanium / silicon dioxide aerogel is prepared according to the following method: adding a titanium precursor and an acid catalyst into a solvent, adding tetraethyl orthosilicate and water after stirring and dissolving, carrying out a sol-gel reaction in a water bath at 60 to 65° C., and aging for 5 to 7 days in a water bath at 50 to 60° C. after the gel is formed to obtain the titanium / silicon dioxide aerogel.

4. The process for preparing lithium iron manganese phosphate material according to claim 3, characterized in that: The molar ratio of water to tetraethyl orthosilicate is (0.8-1):

1.

5. The preparation process of lithium iron manganese phosphate material according to claim 1, characterized in that: The titanium / silicon dioxide aerogel is modified according to the following method: carboxymethyl cellulose is added to a solvent, and after dissolving, the titanium / silicon dioxide aerogel is added, and refluxed at 80-90° C. for 6-8 hours, and finally washed and dried to obtain the titanium / silicon dioxide aerogel modified with carboxymethyl cellulose.

6. The process for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The molar ratio of the phosphorus source, manganese source, iron source and lithium source is 1: (0.3-0.6): (0.4-0.7): (0.95-1.1).

7. A lithium manganese iron phosphate material, characterized in that: The material is prepared according to the preparation process of the lithium manganese iron phosphate material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Doped lithium iron manganese phosphate material, preparation method and application

    CN116259754A

  • Coated separators for electrochemical cells and methods of forming the same

    US20230246295A1